Analysis of the Influence of Product Quality and Distribution Strategy on Sales at PT Temprina Media Grafika Bekasi - Sugiyanta, Yohanes; Rohadi, Muhamad (LPPM of NAROTAMA UNIVERSITY, 2024)
Purpose: This study aims to analyze the Effect of Product Quality (X1), Distribution (X2) of Sales Volume (Y) Study on PT Temprina Media Grafika Bekasi Design/methodology/approach: The data used in this study are primary data. In this study, the sampling method using the Non Probability Sample method is Purposive Sampling. Findings: The results of this study indicate that Product Quality (X1), Distribution (X2) simultaneously have a positive significant effect on Sales Volume (Y) on PT Temprina Media Grafika Bekasi. Paper type: Research Paper